Pengembangan Aplikasi Android Rekomendasi Tempat Pembelian Kuliner Khas Malang dengan GDSS dan LBS - Dheanisa Putri Rahayu; Ratih Kartika Dewi; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Culinary is the result of processed food in the form of food or beverages. One city that has many culinary places is Malang. The number of places for culinary purchases allows tourists to choose the desired culinary spot. However, there is no system that can provide information about where to buy culinary based on the criteria desired by more than 1 user. Based on the problems that have been mentioned above, the researcher wants to create a recommendation system for typical Malang culinary places based on Android. This recommendation system uses the TOPSIS-Borda method through the Group Decision Support System approach. To get a culinary place recommendation, four criteria are needed as a determinant, including the closest distance to a culinary place, operating hours, affordable prices and good ratings. In solving the problem, the researcher uses a web service to store data on culinary places and perform TOPSIS-Borda calculations. The black-box test results show that all functional requirements can operate well with an accuracy level of 100%. For the comparison of manual calculations with calculations from the system, the two calculation results have the same value. For the results of usability testing, this recommendation system gets an average result of 77 which indicates that the system is quite well received with grade C, also having excellent category based on the SUS Score.